Comercialización del banano ecuatoriano al mercado ruso - Vera Guanoluisa, Jennevi Lorena (2024)
Banana cultivation represents one of the most important items in the Ecuadorian economy, in the domestic market it is a generator of sources of employment, mainly in families on the Ecuadorian coast, and in the foreign market bananas are one of the main traditional export products worldwide. Russia is one of the most important markets for the banana sector in Ecuador, accounting for 25 % of its export earnings. There are several factors that explain the recovery of banana exports to Russia, one of them is that certain shipping companies that arrive in Russia, such as MSC, maintain exports of medicines and food. Another is the temporary elimination of the 4 % tariff on bananas on the Russian market, by a decision of the Eurasian Economic Union (EEU). In order to maintain export standards to the Russian market, it is necessary to improve the levels of quality control and phytosanitary products, which will allow in the future not to have inconveniences such as what happened recently with the humpback fly that led to the cancellation of export certificates of 5 banana companies for a period of approximately 15 days. Thanks to the constant dialogue between the two nations and the documentation presented by Agrocalidad, the veto was lifted and the export doors to these companies are reopened.